2020
DOI: 10.3389/fphys.2020.588821
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of the Repeated-Sprint Training in Hypoxia in Tennis

Abstract: PurposeTo examine physiological and technical responses to repeated-sprint training in normobaric hypoxia at ∼3,000 m (RSH, n = 11) or in normoxia (RSN, n = 11) compared to a control group (CON, n = 8) in well-trained tennis players. Participants were 28.8 ± 5.9 years old without any previous experience of training in hypoxia.MethodsIn addition to maintaining their usual training (CON), both RSH and RSN groups completed five tennis specific repeated-shuttle sprint sessions (4 × 5 × ∼8 s maximal sprints with ∼2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 38 publications
1
23
1
Order By: Relevance
“…On the other hand, sprint interval training (SIT) includes repeated long sprints (~30 s) interspaced by longer rest periods (~2–4 min) (Buchheit and Laursen, 2013a , b ; Brocherie et al, 2017 ). In recent years, studies have suggested that the addition of a hypoxic stimulus to chronic SIT and RST may favor several training responses (Faiss et al, 2013 ; Brocherie et al, 2017 ; Brechbuhl et al, 2020 ; James and Girard, 2020 ). For example, systemic hypoxia (HYP) may promote higher muscle perfusion and oxygenation with greater modulations of molecular adaptations (Faiss et al, 2013 ; Brocherie et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, sprint interval training (SIT) includes repeated long sprints (~30 s) interspaced by longer rest periods (~2–4 min) (Buchheit and Laursen, 2013a , b ; Brocherie et al, 2017 ). In recent years, studies have suggested that the addition of a hypoxic stimulus to chronic SIT and RST may favor several training responses (Faiss et al, 2013 ; Brocherie et al, 2017 ; Brechbuhl et al, 2020 ; James and Girard, 2020 ). For example, systemic hypoxia (HYP) may promote higher muscle perfusion and oxygenation with greater modulations of molecular adaptations (Faiss et al, 2013 ; Brocherie et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…A priori power analyses were performed with alpha and beta errors of 0.05 and 0.20, respectively, and a medium effect size (f = 0.25) as it has been observed during these training protocols [4][5][6][7][8][9]. The required sample size was 36 split into four groups.…”
Section: Participantsmentioning
confidence: 99%
“…Similar or higher gains in several variables, including maximal oxygen uptake ( ), muscle oxidative capacity and time trial performance were shown compared to endurance training protocols achieved with higher training volume [ 1 3 ]. The addition of hypoxic stimulus to HIT has been increasingly acknowledged to favor training adaptations [ 4 – 9 ]. Performing exercise bouts under systemic hypoxia reduces arterial oxygen partial pressure and thus increases energy production through substrate-level phosphorylation [ 10 ] and adaptations such as enhanced mitochondrial density, oxidative enzyme activity, and capillary density [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the evidence of any relationship between the HRV and RSA or anaerobic performances is far less clear. Indeed, training-induced improvement of RSA has been associated with either an increase ( Buchheit et al, 2012 ; de Oliveira et al, 2013 ), a decrease ( Buchheit et al, 2012 ; Merati et al, 2015 ) or no changes ( Brechbuhl et al, 2020 ) in parasympathetic activity (root mean square of successive differences (RMSSD) and high frequency (HF) power). Acute hypoxia alters HRV ( Wille et al, 2012 ; Krejčí et al, 2018 ) and may combine with repeated-sprint training to further stress autonomic nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…Acute hypoxia alters HRV ( Wille et al, 2012 ; Krejčí et al, 2018 ) and may combine with repeated-sprint training to further stress autonomic nervous system. To the authors’ knowledge, only one study monitored resting HRV indices before and after RSH but failed to detect an association between performance enhancement and changes in HRV ( Brechbuhl et al, 2020 ). However, the authors did not record HRV during recovery, especially parasympathetic reactivation characterizing fitness level ( Buchheit 2014 ) which was found to increase after repeated-sprint training and high-intensity intermittent training in normoxia ( Buchheit et al, 2008 ; Vernillo et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%